Remodeling of Endothelial Cell Nucleus Exposed to Three Different Mechanical Stimuli - Toshiro OHASHI; Kazuhiko HANAMURA; Daisaku AZUMA; Naoya SAKAMOTO; Masaaki SATO (Journal of Biomechanical Science and Engineering, 2008)
Cell Nuclei play a critical role in controlling gene expression and replicating DNA, and is known to deform in association with cell shape changes in response to external forces. This study dealed with morphological analysis to quantitatively assess the effect of three different mechanical stimuli including fluid shear stress, cyclic stretching, and hydrostatic pressure on nucleus morphology. Fluorescence images showed that fluid shear stress and cyclic stretching induced cell elongation and orientation very specifically to the direction of flow and stretch, respectively. In contrast, hydrostatic pressure induced cell elongation at non-preferred orientation. The nuclei were also found to deform in the same manner as that of the cells, which was, in particular, dependent on the type of mechanical stimuli, possibly suggesting the direct mechanical linkages between cell surface receptors, cytoskeletal meshworks, and nuclei. It was also shown that cytoskeletal meshworks may contribute to pre-existing strain of the nuclei.